The Sinitic encounter in Southeast China through the first millennium CE - Clark, Hugh R. (University of Hawaiʻi Press, 2016)
This work investigates the ancient integration of lands south of the Yangtze River into China and its impact on Chinese culture. For the past 1000 years the south has been the cultural, demographic, and economic centre of China, but the process whereby this was accomplished has long been overlooked. Hugh Clark offers a new perspective on this neglected area of Chinese history.